Programas europeos y desarrollo rural en Cantabria. Actuaciones y perspectivas = European programs and rural development in Cantabria. Performances and perspectives (Polígonos. Revista de Geografía, 2013)
El artículo se centra en analizar la influencia y la repercusión de la política europea de desarrollo regional y local en el medio rural de Cantabria a lo largo de la década de los 90 y en especial a partir de la clasificación de la región como Objetivo 1, hecho que ha sucedido en la segunda mitad de la década.This article focuses on analysing the influence and effect of European politics for regional and local development on the rural area of Cantabria during the nineties and especially starting from the classification of region as aim 1. This event has taken place in the second half ofthe decade.